Do digital competencies and social support boost work engagement during the COVID-19 pandemic? - Oberländer, Maren; Bipp, Tanja (Computers in human behavior, 2022)
In today's world of work, the need for digital communication and collaboration competencies became even more prevalent during the ongoing COVID-19 pandemic. Yet, research and practice are lacking solid measurement instruments assessing digital communication and collaboration competencies of workers so far. Furthermore, it is yet unknown if digital communication and collaboration competencies and other so far known resources indeed act as drivers of work engagement during the pandemic. Based on the Job Demands-Resources (JD-R) model and the conservation of resources theory, we hypothesized that personal (digital communication and collaboration competencies) and job (social support) resources positively influence each other over time, also boosting work engagement. In a cross-lagged study design during the pandemic, we investigated our hypotheses in a sample of German workers (N = 231). Against our expectations, we did not find support for effects from personal or job resources on work engagement over time or effects of the resources influencing each other. Instead, we found high stabilities of digital communication and collaboration competencies and work engagement. Our results provide important insights into the motivational process of individuals working during a pandemic. The theoretical and practical implications for the JD-R model in times of crisis are discussed.